(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article analizes three novels of indigenous referent (Cailloma, A orillas del Bío-Bío, Gualda) published in the 1870s. The novels use the heroic and evangelist paradigms Ercilla’s La araucana and Núñez de Pineda’s Cautiverio feliz, respectively. They represent pre-republican times, utilizing romantic literary strategies to mystify Mapuche reality for the construction of an epic past that meets the demands of the historical moment in which they are published. These catholiccriollo authors attempt to vindicate the “native soul’ in order to “save the man” and not the ethnicity, which they consider anachronical according to modernity’s law of evolution. Finally, these texts fit into Andrés Bello’s construction of Chilean national identity based on the Mapuche’s past as told in La araucana, and the appropriation of Mapuche heroism as a foundational myth in the new order of the nation-state. This process institutes itself through the denial of indigenous society and its right to define itself and maintain its worldview and autonomy in the face of the establishment of the criollo entity that imposes itself as a universal in the occupied lands.